Array ultrasonic guided wave spiral focusing detection method for inner damage of messenger cable in covered area. (1st April 2023) - Hong, Xiaobin; Lin, Jinfan; Zhou, Jianxi; Yang, Dingmin
Graphical abstract: Abstract: The messenger cable damage detection of catenary system is one of the important safeguard to ensure the safe operation of electrified railways. Due to the multi-layer and opposite spiral direction structure of the messenger cable, the ultrasonic guided wave dispersion curve is difficult to obtain, and the inner layer damage signal is too weak to identify. A novel array ultrasonic guided wave spiral focusing detection method is proposed for the inner layer damage of messenger cable in covered area. Firstly, the dispersion curves of ultrasonic guided waves in the messenger cable were calculated by semi-analytical finite element based on twisted coordinate system, and the multi-modal propagation characteristics were analyzed. Secondly, the path differences from guided wave array elements to inner layer were studied to get the adjustment matrix of spiral focusing. Thirdly, the inner damage information was extracted from spiral focusing signal by cross sparse representation based on dispersion dictionary, and the damage autofocus imaging was realized by bi-directional time reversal imaging. Finally, the spiral focusing enhancement effect and identification imaging effect of inner layer damage were analyzed and verified through simulation and experiments. The results show that, compared with the normal superimposed method, the damage signal indexes of sub-outer layer and the center layer are increased by 32.2% and 40.8% respectively after spiral focusing. The inner layer damage signal of the spiral focusing method has a higher recognition rate and good anti-interference ability, and the damage imaging has low sensitivity to threshold value and has no damage artifacts.